POWER OF SOFT SKILLS DETERMINING ACADEMIC CAREER SATISFACTION: EMPIRICIAL STUDY ON RESEARCH ASSISTANTS - (:unkn) unknown (PRESSACADEMIA, 2016)
Recent debate on skill acquisition by employees focuses on skill shortages (lacking required skills) and skills gaps (lack proficiency in the job) (Hurrell, 2015). Technical skills are not only ones considered in this context. As mostly discussed in literature, performing a job requires several technical skills that are acquired by knowledge in cognitive sense and influenced by an individual's intelligence. However, such skills are not enough for today, there is a need to have interpersonal, human, people or behavioral skills in order to apply technical ones in the workplace (Weber, Finley, Crawford, Rivera, 2009) that are not reliant on abstract reasoning, are involving interpersonal and intrapersonal abilities to facilitate mastered performance in particular contexts (Hurrell, Scholarios and Thompson, 2012). Thus, technical skills are discussed to complement with soft skills such as human, conceptual, interpersonal and leadership etc. to allow the proper expression, implementation and collaboration of knowledge assets (Brill, Gilfoil and Doll, 2014; Weber, Crawford, Lee and Dennison, 2013). Even there is not a precise taxonomy of such skills; in literature four categories are mostly used to define them as leadership/people/relationship; communication; management and organization, cognitive skills and knowledge (Kantrowitz, 2005). In this context, the ultimate aim of this study is to discuss whether academician's soft skills (e.g. communication, interpersonal relations, openmindness, positive attitudes, teamwork, creativity etc.) have an impact on their satisfaction from their career. This study also argues that without having soft skills, how a prospective academician, here Research Assistants, could prepare his students for the future demanding more than technical skills in order to manage themselves and their careers. Proposed sample consists of research assistants who are working in a state university located in Istanbul. The importance of this study lies in the changing role of educational institutions especially universities and the changing role of academia as well.
Keywords: Soft skills; Career Satisfaction; Academia